Educação e direitos humanos : trajetórias de Porto Alegre no enfrentamento à violência sexual contra crianças e adolescentes - Machado, Cláudia (2014)
This thesis discusses the strategies of the network for child and adolescent victims of sexual violence identified in Porto Alegre, with a mapping of communication flows through the analysis of log devices and existing communication network. In this sense, observing the connections between the different areas through the following questions: How do you organize the flow of care for children and adolescents identified as victims of sexual violence? How are the instruments of record received in these cases? How to build a communicative mesh for child and adolescent victim s network? How to prevent sexual violence against children and adolescents aim is to reflect on the role of schools and education professionals about this topic? The research is justified as it seeks to discover how to present the actions related to "Against Sexual Violence," from a critical stance on how we understand the issues related to the topic in various areas, the practices of education, health, security and human rights, which is one among many possibilities.